2014
DOI: 10.1038/srep06841
|View full text |Cite
|
Sign up to set email alerts
|

HnRNP C, YB-1 and hnRNP L coordinately enhance skipping of human MUSK exon 10 to generate a Wnt-insensitive MuSK isoform

Abstract: Muscle specific receptor tyrosine kinase (MuSK) is an essential postsynaptic transmembrane molecule that mediates clustering of acetylcholine receptors (AChR). MUSK exon 10 is alternatively skipped in human, but not in mouse. Skipping of this exon disrupts a cysteine-rich region (Fz-CRD), which is essential for Wnt-mediated AChR clustering. To investigate the underlying mechanisms of alternative splicing, we exploited block-scanning mutagenesis with human minigene and identified a 20-nucleotide block that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Zn 2 SnO 4 (ZTO) is an important n-type transparent conducting oxide, which has been attracting intense interest due to its outstanding performance and potential use in applications such as optoelectronic devices, anode materials for dye-sensitized solar cells, and photocatalysts for the degradation of organic pollutants8910. At ambient conditions, ZTO crystallizes into a typical inverse spinel structure with the Fd 3 m space group111213.…”
mentioning
confidence: 99%
“…Zn 2 SnO 4 (ZTO) is an important n-type transparent conducting oxide, which has been attracting intense interest due to its outstanding performance and potential use in applications such as optoelectronic devices, anode materials for dye-sensitized solar cells, and photocatalysts for the degradation of organic pollutants8910. At ambient conditions, ZTO crystallizes into a typical inverse spinel structure with the Fd 3 m space group111213.…”
mentioning
confidence: 99%
“…Dissection of p.E415G in exon 16 of COLQ revealed that SRSF1 is essential for inclusion of constitutive exon 16 [12]. Dissection of IVS3-8G>A in intron 3 of CHRNA1 [21] and P3A23'G>A in exon P3A of CHRNA1 [22] disclosed that alternative skipping of exon P3A is mediated by hnRNP H, PTBP1, and hnRNP L. Although the analysis was not based on CMS mutations, we found that HnRNP C, YB-1, and hnRNP L cooperatively enhance skipping of MUSK exon 10 and make a Wnt-insensitive MuSK isoform [28]. Splicing mutations prompted us to dissect the underlying mechanisms associated with the mutations.…”
Section: Resultsmentioning
confidence: 70%
“…MUSK exon 10 is alternatively spliced in human but not in mouse [28]. MuSK mediates AChR clustering at the motor endplate and exon 10 encodes a frizzled-like cysteine-rich domain (Fz-CRD), which is essential for Wnt-mediated AChR clustering.…”
Section: Hnrnp C Yb-1 and Hnrnp L Cooperate To Make A Wntinsensitivmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Binding of hn RNP C to RNA enhances binding of YB ‐1 and hn RNP L to the immediate downstream sites and enhances skipping of exon 10 (Nasrin et al . ). The indicated cis ‐element starts from 81 nucleotides downstream of the intron 9/exon 10 junction, and ends at 165 nucleotides upstream of the exon 10/intron 10 junction.…”
Section: Alternative Splicings At X Y and Z Sites Of The Agrin Genementioning
confidence: 97%